The relevance of ADCC for EGFR targeting: A review of the literature and a clinically-applicable method of assessment in patients. Issue 2 (August 2015) - Monteverde, Martino; Milano, Gerard; Strola, Giuliana; Maffi, Monica; Lattanzio, Laura; Vivenza, Daniela; Tonissi, Federica; Merlano, Marco; Lo Nigro, Cristiana
Highlights Ex vivo ADCC answer can be related to donor effector cell. LDH assay could be used for ADCC testing. We exclude frozen PBMC as best candidates for ADCC test. In chemotherapeutic regimen a fixed number of NK should be evaluated for ADCC.